Developing the Ability to Design a Residential House through an Interior Textbook Integrated with Research Results - Agustin, Dyan; Anggriani, Niniek; Azzahra, Tasya; Ayu K, Sabrina (Future Science, 2020)
This textbook discusses the principles used in designing an interior / interior environment in a building. The building which is the object of discussion is the residence. This is intended so that students have provisions in designing space in the interior of a residence. Residential houses have efficiency in terms of design because if they are not designed properly it will cause discomfort in living. The things that will be discussed include, how to organize the space in a residence, how to choose colors that can create a broad and aesthetic impression, how to design good and ergonomic furniture that suits the house. The method is used in two stages, namely the creation stage and the publication stage. The creation stage includes pre-production, production and, post-production. Meanwhile, the publication stage includes book publishing, book launching, and textbook copyright management. This textbook will be useful for students of the Architecture study program Interior and Architectural Design 3. It is hoped that students will understand more about the interior of a residence with an explanation and accompanied by examples from the results of previous research.